Enacting objects and subjects in a children's rehabilitation clinic: Default and shifting ontological politics of muscular dystrophy care. (July 2022) - Thille, Patricia; Abrams, Thomas; Gibson, Barbara E
In health care clinics, problems are constructed through interactions, a choreography of human and non-human actors together enacting matters of concern. Studying the ways in which a body, person, family, or environment is objectified for clinical purposes opens discussion about advantages and disadvantages of different objectification practices, and exploration of creative ways to handle the diversity and tensions that exist. In this analysis, we explored objectifications in a Canadian neuromuscular clinic with young people with muscular dystrophy. This involved a close examination of clinical objectification practices across a series of 27 observed appointments. We identified the routinised clinical assessments, and argue these embed a default orientation to how to intervene in people's lives. In this setting, the routine focused on meeting demands of daily activities while protecting the at-risk-body, and working toward an abstract sense of an independent future for the person/body with muscular dystrophy. But the default could be disrupted; through our analysis of the routine and disruptions, we highlight how contesting visions for the present and future were consequential in ways that might be more than what is anticipated within rehabilitation practice.